Single-cell RNA sequencing of the spleen reveals differences in Salmonella typhimurium infection mechanisms between different chicken breeds - Qi Zhang; Qiao Wang; Jumei Zheng; Jin Zhang; Gaomeng Zhang; Fan Ying; Dawei Liu; Jie Wen; Qinghe Li; Guiping Zhao (Poultry Science)
Bacterial infections remain an important cause of morbidity in poultry production. The molecular characteristics and dynamic changes in immune cell populations after bacterial infection have yet to be fully understood. Beijing-You chicken and Cobb broiler, two broiler breeds with different disease resistance, were infected with Salmonella typhimurium, and inflammation models were constructed. Compared to Beijing-You, Cobb showed higher survival rates, lower liver load, and milder spleen damage after Salmonella infection. We characterized chicken spleen CD45+ immune cells by single-cell RNA sequencing and identified 9 distinct cell types among 54,487 cells. In Beijing-You, mono-macrophages expressed higher levels of pro-inflammatory factors, including IL1B, IL6, and M-CSF, after bacterial infection. In Cobb, Tregs exhibited intense inflammatory inhibition and highly expressed CTLA4, LAG3 and other immunosuppressive regulators. In addition, we found complex macrophage phenotypes during bacterial infection, with a tendency in macrophages from pro-inflammatory phenotypes (Mac-IL1B) to anti-inflammatory phenotypes (Mac-C1QC/Mac-MARCO). This study represents the first single-cell transcriptomic analysis of chicken spleen and compares the immune responses of Beijing-You and Cobb after bacterial infection. These findings provide insight into the mechanism of inflammation regulation in different broiler breeds.